Pengaruh Religiusitas, Kualitas Layanan, dan Promosi Terhadap Minat Menabung di Bank Syariah - Hilmi Musyaffa; Muhammad Iqbal (Perbanas Institute, 2022)
This study aims to analyze the effect of religiosity, service quality, and promotion on interest in saving in Islamic banks. The research uses a quantitative approach with multiple linear regression analysis techniques as the data analysis method. Data collection using purposive sampling technique with a Muslim population domiciled in Central Jakarta. The results obtained from this study show that religiosity and service quality do not affect interest in saving, while promotion affects interest in saving. The religiosity of a Muslim does not affect the person's interest in saving in Islamic banks. Likewise, the quality of services from Islamic banks does not determine a Muslim's interest in saving. Promotion is the only factor in this study that encourages a Muslim's interest in saving in Islamic banks. The high promotion of a Muslim about Islamic banking will increase that person's interest in saving in Islamic banks. Keywords: Religiosity, Service quality, Promotion, Interest in saving